Problematic Shopping Behavior: An Item Response Theory Examination of the Seven-Item Bergen Shopping Addiction Scale. - Zarate, Daniel; Fullwood, Lana; Prokofieva, Maria; Griffiths, Mark D.; Stavropoulos, Vasileios (International Journal of Mental Health & Addiction, 2023)
There has been an increasing amount of research examining problematic shopping behavior (PSB), often referred to in the psychological literature as "compulsive buying" or "shopping addiction." A popular scale for assessing the risk of PSB is the seven-item Bergen Shopping Addiction Scale (BSAS). To expand our knowledge of the psychometric properties of this instrument, the present study employed Item Response Theory (IRT) and differential item functioning analyses (DIF) while concurrently attempting to determine a preliminary cut-off point. A relatively large community sample completed the BSAS online (N = 968, M = 29.5 years, SD = 9.36, 32.5% women). IRT analyses showed differences regarding the BSAS items' discrimination, difficulty, and precision, with a raw score exceeding 23 (out of 28) indicating a higher risk of shopping addiction. Finally, while most BSAS items operated equally among males and females, Item 2 (mood modification) required a higher level of shopping addiction behaviors to be endorsed by males. The BSAS functions as a reliable assessment of the risk of shopping addiction, particularly between average and high levels of the trait. Clinical implications are discussed in light of these findings.